2007
DOI: 10.1097/cad.0b013e3280678042
|View full text |Cite
|
Sign up to set email alerts
|

Radioimmunotherapy of refractory or relapsed Hodgkin's lymphoma with 90Y-labelled antiferritin antibody

Abstract: The aim of this study was to evaluate the safety and efficacy of radiolabelled rabbit polyclonal antiferritin antibody in relapsed or refractory Hodgkin's lymphoma. The protocol included a first intravenous injection of In-labelled antiferritin antibody, followed by immunoscintigraphy at 4, 48 and 72 h, and an intravenous injection of Y-labelled antiferritin antibody in the case of tumour targeting. Ten patients were included in the study: median number of chemotherapy regimens: 3; number of autografted patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…A new antibody (In‐labelled antiferritin antibody) has recently become available and was given, by injection (at 11·84 MBq/kg), to nine patients followed by immunoscintigraphy. One CR and six PR were observed with a median duration of response of 8 months (Decaudin et al , 2007). A prospective multicentric with a dose‐escalation is ongoing in this setting.…”
Section: New Agentsmentioning
confidence: 99%
“…A new antibody (In‐labelled antiferritin antibody) has recently become available and was given, by injection (at 11·84 MBq/kg), to nine patients followed by immunoscintigraphy. One CR and six PR were observed with a median duration of response of 8 months (Decaudin et al , 2007). A prospective multicentric with a dose‐escalation is ongoing in this setting.…”
Section: New Agentsmentioning
confidence: 99%
“…Similarly, in a group of 90 patients with relapsed HL (median of 4 prior therapies, with 75% having failed stem cell transplantation), response rates ranging from 20% to 86% were achieved depending on dose and timing; fractionation did not reduce hematologic toxicity or improve the antitumor effect [87]. More recently, a study of 10 patients with relapsed/ refractory HL treated with 90 yttrium-labeled antiferritin antibody was reported [89]. The toxicity profile, overall response rate of 70% (on intent-to-treat analysis), and median response duration of 8 months mirror the results of earlier investigations.…”
Section: Radioimmunotherapymentioning
confidence: 99%
“…Clinical experience with radioimmunotherapy in HL had previously centered upon polyclonal antiferritin antibodies conjugated to either 131 iodine or 90 yttrium. Radiolabeled polyclonal antiferritin antibodies, with or without autologous stem cell infusion, have been investigated clinically in a number of early phase trials [84][85][86][87][88][89] based on the finding that ferritin is a tumor-associated antigen [90]. These early phase, generally older trials, published in the mid-1980s and 1990s, demonstrated some antitumor activity in the relapsed/refractory setting.…”
Section: Radioimmunotherapymentioning
confidence: 99%
“…The tumor-associated protein ferritin has been used as a target [69]. 90 Y-labeled rabbit polyclonal antiferritin antibody has been shown to be well tolerated and have disease activity in relapsed Hodgkin lymphoma [70]. 131 I-labeled murine anti-CD30 monoclonal antibody (Ki-4) was given to 22 patients with relapsed or refractory CD30-positive Hodgkin lymphoma [71].…”
Section: Novel Therapiesmentioning
confidence: 99%